Enhancing the efficiency of Sorghum and Groundnut improvement in Nigeria - Echekwu, C.A; Abdulmalik, Rekiya O.; Zarafi, Afiniki B.; Adamu, Rabiu S.; Ahmed, H.O.; Ahmad Yahaya, Muhammad; Usman, M.; Sami, R.A. (International Maize and Wheat Improvement Center, 2024)
Strong collaborations with ADCIN, CIMMYT, private sector stakeholders, and research institutions have facilitated knowledge exchange, technology adoption, and the development of innovative solutions tailored to farmers' needs and industry demands.